Evaluating the Sekolah Penggerak Program’s Effectiveness in Developing the Pancasila Students Profile in Primary School - Evi Nur Fajri; Sri Marmoah; Tri Murwaningsih (STAI Hubbulwathan Duri, 2024)
This study investigates the implementation of the Project for Strengthening the Profile of Pancasila Students in the Sekolah Penggerak program at SD Negeri Wonorejo, Sukoharjo Regency, during the 2022/2023 academic year. The project aimed to enhance student creativity and independence through project-based learning. A qualitative descriptive method with a case study approach was employed. Participants included the school principal, fourth-grade teachers, and subject teachers for grades I-VI. Data were collected through interviews, observations, and document analysis. Project planning was conducted collaboratively, although challenges such as limited modules and evaluation instruments persisted. Themes of entrepreneurship and local wisdom contextualized learning and guided project implementation. The project followed a structured process, including material preparation, group division, topic introduction, product creation, and reflection. These stages fostered increased creativity and independence among students. Evaluation was based on process observations and project reports assessed with progress predicates. The project also positively engaged parents but faced obstacles like time management and theme selection difficulties. The findings highlight the need for contextual modules, valid evaluation instruments, teacher training, stronger external collaborations, and principal supervision. Support from the Education Department in the form of policy and facilities is essential to optimize project outcomes. The project demonstrated success in enhancing student creativity and independence while addressing contextual challenges. Future research should focus on developing practical evaluation tools tailored to students’ needs and the school context, ensuring sustained impact and scalability.